Inhibitory activity and toxicity of Cordyceps nidus lyophilized extracts (2018)
Cordyceps is a genus of fungal entomopathogens, which is currently studied because of its potential in pharmaceutic applications. Cordyceps nidus (Hypocreales: Cordycipitaceae) is a parasite of young trapdoor spiders (Mygalomorpha) in rainforests from Neotropics. This species is phylogenetically related to Cordyceps militaris and Cordyceps pruinosa, which are traditionally used because of their medicinal properties. Previous metabolomics assays and some biological activity analyses have shown unique biochemical characteristics of C. nidus. Although, this species has a strong potential in the industry of natural products, the toxicity of its extracts has to be deeply determined in order to understand the safety of its application. So, we aimed to evaluate the cytotoxicity and genotoxicity of C. nidus methanolic extracts. Additionally, we also aimed to prove the bactericidal effect with a different method than the one used before, due to its reported activity against several gram-positive bacteria. Results showed that there is a negative...